ACUTE KIDNEY INJURY IN NEONATES AND NEUTOPHILIC GELATINOUS ASSOCIATED LIPOCALIN AS EARLY BIOMARKER - Timovska Naunova, Silvana; Babinkostova, Zoja; Jordanova, Olivera; Sofijanova, Aspazija (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
Objective : Acute kidney injury (AKI) is a serious problem in neonates in intensive care units. It is defined as a rapid decrease in glomerular filtration that leads to retention of creatinine and nitrogenous waste products and usually with a decrease in urine output. NGAL represents the most promising biomarker for early detection of kidney injury. It can detect the kidney injury in the first 2 to 3 hours of its occurrence, even before there is a decrease in urine output and an increase in sCr. The aim of the study was to determine the role of biomarker NGAL in early detection of kidney injury in neonates.  Methods.   The study evaluated the neonates suffering kidney injury who at the period of three years were treated at the University Children's Hospital in Skopje. All cases of neonates with kidney injury were analyzed according to gender, gestational age, birth weight and risk factors such as asphyxia, sepsis, prematurity, meconium plug syndrome and congenital heart diseases. NGAL was analyzed in urine samples collected on two occasions (day of admission and 2 days later) and the concentration of NGAL was determined using NGAL ELISA KIT (Bioporto). Medical data records of admitted neonates with AKI were analyzed. The material was statistically processed using methods of descriptive statistics. Results. The study was carried out at the neonatal intensive care unit at the University Children's Hospital  Skopje in which neonates  with documented acute kidney injury were evaluated. The whole study has been performed during the 3 year period. The estimated prevalence of AKI in neonates was 6.4%. Most of the involved neonates in the study were born at term (68%) with predominance of male neonates (64%). The analyzed results showed a higher values of urinary NGAL on the day of admission (373.8 ± 194.9) and a slight upward trend, with  further increase in the third day after admission (439.4 ± 254, 7). There was a significant difference between the uNGAL values and sCr values on the day of admission of neonates in NICU, p<0,001. The mean urinary NGAL values in neonates with AKI with lethal outcome were 586.39 ± 182.3 while the mean values in neonates without lethal outcome was 254.22 ± 28.5. This difference was statistically significant (p<0,001).  Conclusion : Early, biomarker based identification of neonates at risk of kidney injury is a fundamental step toward AKI prevention. NGAL has ability to predict AKI before clinical signs are evident and can facilitate implementation of appropriate preventive measures and improve resource utilization.  Its use allows us to make the right clinical decisions at the right time, before the illness is clinically manifest and take appropriate measures to prevent renal function decline.